Public water supply distribution systems : assessing and reducing risks, first report (National Academies Press, 2005)
The purpose of this report is to identify trends relevant to the deterioration of drinking water quality in water supply distribution systems, using available information, and to identify and prioritize issues of greatest concern for distribution systems based on review of published material.